KERJA SAMA BILATERAL DALAM KERANGKA PENYELESAIAN MASALAH NELAYAN PELINTAS BATAS PERAIRAN INDONESIA-AUSTRALIA - Ratna lndrawasih; Ary Wahyono (Research Centre for Population, Indonesian Institute of Sciences, 2010)
Traditional fisherman conducting their fishing activities as part of their long term .fishing tradition is recognized and allowed to catch fish under the MoU Box 1974 between the government Australia and Indonesia. As a normative rule, there is no serious problem with this arrangement. However, in the meantime Australian government is taken different perspective and interpretation to the definition of traditional fishers. Traditional interpretation of the MoU Box 197 4 which does not correspond with the facts on the ground this is the beginning of the fishermen issue border crossers Indonesia Australian waters. Recently the traditional fisherman have shifted become cross border which violated Mou Box 1974. Meanwhile, bilateral cooperation was initiated by both countries to resolve the problems of traditional fishermen do not give results because the solution is more charity, namely the empowerment of fishermen in the area of origin. This solution is considered a form of